Association of serum cytokines with oral HPV clearance. (July 2016) - Lam, Jennifer O.; Bream, Jay H.; Sugar, Elizabeth A.; Coles, Christian L.; Weber, Kathleen M.; Burk, Robert D.; Wiley, Dorothy J.; Cranston, Ross D.; Reddy, Susheel; Margolick, Joseph B.; Strickler, Howard D.; Wentz, Alicia; et al.
Highlights: Higher serum TNF-α concentration was associated with reduced oral HPV clearance. The association of TNF-α with oral HPV clearance was stronger among men than women. Results are consistent with studies of TNF-α and decreased cervical HPV clearance. Abstract: Background: Initial studies suggest higher serum levels of some pro-inflammatory cytokines may be associated with decreased cervical human papillomavirus (HPV) clearance. However, the relationship of cytokines with oral HPV clearance has not been explored. Methods: From 2010 to 2014, oral rinse and serum samples were collected semi-annually from 1601 adults. Oral rinse samples were tested for HPV DNA using PCR. Based on oral HPV results, 931 serum samples were selected for cytokine evaluation to include a roughly equal number of prevalent (n = 307), incident (n = 313), and no oral HPV infections (n = 311). Electrochemiluminescence multiplex assays were used to determine the concentrations of IL-6, IL-8, TNF-α, IFN-γ, IL-1β, IL-2, IL-4, IL-10, IL-12 and IL-13. The relationship between serum cytokine concentrations (categorized into quartiles) and oral HPV clearance was evaluated with Wei-Lin-Weissfeld regression models, adjusting for HPV infection type (prevalent vs. incident), age, HIV status, and CD4 T cell count. Results: Higher TNF-α concentration was associated with decreased clearance in men (highest vs. lowest quartile, adjusted hazard ratio [aHR] = 0.52, 95% CI = 0.34–0.79) and women (aHR = 0.76, 95% confidence interval [CI] = 0.55–1.04), with stronger associations in men than women (p-interaction = 0.049). Higher IL-2 concentration was associated with reduced clearance in men (aHR = 0.69, 95% CI = 0.50–0.95), but not women (p-interaction = 0.058). Results were similar within CD4 T cell strata (CD4 ⩾ 500 or CD4 < 500 cells/μl) among HIV-infected participants. No other cytokines were associated with clearance. Conclusion: High serum TNF-α is associated with reduced clearance of oral HPV infection.